Conflicts Between Neighbors: Viticulturists and Soybean Farmers at the Pampa Biome â€“ RS, Brazil - Nodari, Eunice Sueli (Fronteira: Journal of Social, Technological and Environmental Science, 2022)
The Pampa Biome represented in last four centuries a specialization in cattle production, with high historical, socioeconomic, and cultural similarities between Argentina, Brazil, and Uruguay, the countries that share the same Biome. However, from the twentieth century onward the scenario changed. Agriculture and forestry, because of the higher and faster financial returns are now the most important in socio and economic levels. From 2000 onward, a movement of expansion in Brazilian viticulture has highlighted new potential borders, in this case, replacing natural pastures in the Pampa Biome. The significant growth of grapevine area can be illustrated by the doubled surface, reaching 1560 hectares, and the number of vineyards grew from 7 to more than a 100. In 2010 it was created the association â€œVinhos da Campanhaâ€ to represent the region, to structure the geographical indication and to improve the visibility of this terroir and their physical and environmental conditions. However, viticulturists did not expect a huge threat to their vineyards. In the seven past years, the 2,4-D based herbicides spread over transgenic soybean plants cultivated nearby vineyards is causing the decrease of fruit production, presence of herbicide residue in harvested fruit, killing parts or even the entire vineyards: all damages representing monetary losses. Finally, due to the losses and the underway lawsuits, the community cohesion has been broken apart: viticulturists increased cohesion and union among themselves, but social cohesion between them and soybean growers no longer exist in several areas of Rio Grande do Sul state. Later on similar scenario reached other Brazilian States and other fruit species.